Prospective Randomized Observational Pilot Trial Evaluating the Effect of Different Durations of Interdisciplinary Early Intervention and Family Support in Parents of Very Low Birth Weight Infants (Early Bird Study) - Resch, Bernhard; Hofbauer-Krug, Claudia; Pansy, Jasmin; Prechtl, Karin; Avian, Alexander; Kurz, Ronald (Frontiers in Public Health, 2020)
Background: Early childhood intervention (ECI) is a holistic approach for infants with or at risk for psychomotor and/or cognitive and/or behavioral impairment that aims to optimally promote them and positively influence their neurodevelopmental outcome. The right dosage of intervention and when the intervention should start still has to be determined. Hypothesis: Parents are more satisfied when the duration of ECI is longer (120 minutes once a week) than the usual 90 minutes sessions. Methods: We developed a parental questionnaire (both mother and father) which depictured the level of satisfaction of parents with the intervention. We compared 120 with 90 minutes ECI per week during the school year 2017/18. Included were parents of very low birth weight infants (<1500 grams) following informed consent. ECI was initiated at the age of ≥ 2 weeks of the infant at the NICU. Parents were randomized via https://www.randomizer.at/ to 120 or 90 minutes duration and had to answer the questionnaire to the approximate time points of 1, 3 and 6 months. Answers were classified according to the Likert scales. Results: Eleven fathers (55%) and 19 mothers (95%) of the 10 parents of each group participated in the study. Demographic data did not differ between groups and median time-points of questionnaire´ answers were 77, 137, and 220 days, respectively. Overall 120 minutes were not superior to the 90 minutes ECI sessions for both parents regarding parental satisfaction during the study time. We found no differences between fathers and mothers and minimal changes over time. All parents were satisfied with the ECI professionals irrespective of ECI duration. Conclusion: ECI duration of 120 minutes once per week was not superior to 90 minutes duration regarding parental satisfaction with ECI professionals and their work.